Theoretical Antecedents of Standing at Work: An Experience Sampling Approach Using the Theory of Planned Behavior - M. Renée Umstattd Meyer; Cindy Wu; Shana M. Walsh (AIMS Press, 2016)
Time spent sitting has been associated with an increased risk of diabetes, cancer, obesity, and mental health impairments. However, 75% of Americans spend most of their days sitting, with work-sitting accounting for 63% of total daily sitting time. Little research examining theory-based antecedents of standing or sitting has been conducted. This lack of solid groundwork makes it difficult to design effective intervention strategies to decrease sitting behaviors. Using the Theory of Planned Behavior (TPB) as our theoretical lens to better understand factors related with beneficial standing behaviors already being practiced, we examined relationships between TPB constructs and time spent standing at work among "positive deviants" (those successful in behavior change). Experience sampling methodology (ESM), 4 times a day (midmorning, before lunch, afternoon, and before leaving work) for 5 consecutive workdays (Monday to Friday), was used to assess employees' standing time. TPB scales assessing attitude (α = 0.81-0.84), norms (α = 0.83), perceived behavioral control (α = 0.77), and intention (α = 0.78) were developed using recommended methods and collected once on the Friday before the ESM surveys started. ESM data are hierarchically nested, therefore we tested our hypotheses using multilevel structural equation modeling with Mplus. Hourly full-time university employees (n = 50; 70.6% female, 84.3% white, mean age = 44 (SD = 11), 88.2%in full-time staff positions) with sedentary occupation types (time at desk while working ≥6 hours/day) participated. A total of 871 daily surveys were completed. Only perceived behavioral control (β = 0.45, p < 0.05) was related with work-standing at the event-level (model fit: just fit); mediation through intention was not supported. This is the first study to examine theoretical antecedents of real-time work-standing in a naturalistic field setting among positive deviants. These relationships should be further examined, and behavioral intervention strategies should be guided by information obtained through this positive deviance approach to enhance perceived behavioral control, in addition to implementing environmental changes like installing standing desks